Health expenditure of employees versus self‐employed individuals; a 5 year study. (27th August 2020) - Herber, Gerrie‐Cor; Schipper, Maarten; Koopmanschap, Marc; Proper, Karin; van der Lucht, Fons; Boshuizen, Hendriek; Polder, Johan; Uiters, Ellen
Abstract: It is unclear to what extent self‐employed choose to become self‐employed. This study aimed to compare the health care expenditures—as a proxy for health—of self‐employed individuals in the year before they started their business, to that of employees. Differences by sex, age, and industry were studied. In total, 5, 741, 457 individuals aged 25–65 years who were listed in the tax data between 2010 and 2015 with data on their health insurance claims were included. Self‐employed and employees were stratified according to sex, age, household position, personal income, region, and industry for each of the years covered. Weighted linear regression was used to compare health care expenditures in the preceding (year x –1) between self‐employed and employees (in year x ). Compared with employees, expenditures for hospital care, pharmaceutical care and mental health care were lower among self‐employed in the year before they started their business. Differences were most pronounced for men, individuals ≥40 years and those working in the industry and energy sector, construction, financial institutions, and government and care. We conclude that healthy individuals are overrepresented among the self‐employed, which is more pronounced in certain subgroups. Further qualitative research is needed to investigate the reasons why these subgroups are more likely to choose to become self‐employed.